2008
DOI: 10.1038/nature06884
|View full text |Cite
|
Sign up to set email alerts
|

The complete genome of an individual by massively parallel DNA sequencing

Abstract: The association of genetic variation with disease and drug response, and improvements in nucleic acid technologies, have given great optimism for the impact of 'genomic medicine'. However, the formidable size of the diploid human genome, approximately 6 gigabases, has prevented the routine application of sequencing methods to deciphering complete individual human genomes. To realize the full potential of genomics for human health, this limitation must be overcome. Here we report the DNA sequence of a diploid g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

24
1,176
4
23

Year Published

2009
2009
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 1,571 publications
(1,227 citation statements)
references
References 21 publications
24
1,176
4
23
Order By: Relevance
“…Another commonly used approach is to apply quality filters that are aimed at selectively removing errors. Every whole-genome sequence reported so far has used filtering to some extent: the most commonly used filters being those that remove sequences with a too-low coverage depth, discard variants with a low-confidence score or eliminate variants located within a cluster of variants 3,7,[10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] . Surprisingly, there is little consensus with respect to which filters should be used and at which threshold they should be applied.…”
mentioning
confidence: 99%
“…Another commonly used approach is to apply quality filters that are aimed at selectively removing errors. Every whole-genome sequence reported so far has used filtering to some extent: the most commonly used filters being those that remove sequences with a too-low coverage depth, discard variants with a low-confidence score or eliminate variants located within a cluster of variants 3,7,[10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] . Surprisingly, there is little consensus with respect to which filters should be used and at which threshold they should be applied.…”
mentioning
confidence: 99%
“…So far, seven human diploid genomes have been fully sequenced, and some important insights have been gained from these resequencing studies. [145][146][147][148][149][150][151] The most prominent finding from these studies is that, besides SNPs, other genetic variants are also abundant in the human genome. These studies found that in addition to the 3-4 million SNPs, several hundred-thousand of short indels (for example, sizes defined as 3 and 16 bp or less in the Bentley et al 147 and Wang et al 148 study, respectively) are also present in each individual human genome.…”
Section: Human Genetic Variationmentioning
confidence: 99%
“…As such, the remaining several hundred thousands of indels in the range of several nucleotides to tens of nucleotides, which were identified in the recent whole genome resequencing experiments, do not currently have their own category. [27][28][29][30][31][32][33] For example, Wang et al (2008) 29 found B140 000 indels within 1-3 bp in the Han Chinese YH genome, and B400 000 indels defined from 1 to 16 bp were also detected in the African NA18507 genome by Bentley et al (2008). 30 Perhaps a new category such as 'short indels' needs to be created to fit them in, and those indels between 100 bp to 1 kb should probably be renamed as 'intermediate indels' (Figures 1c and d).…”
Section: Categories Of Genetic Variationsmentioning
confidence: 99%
“…2 However, the richness of genetic variations in the human genome has recently been further corroborated by the several whole genome resequencing studies, revealing plenty of new SNPs, indels, CNVs and other structural variations. [27][28][29][30][31][32][33] The technological developments have facilitated and accelerated the process of identifying genetic variations, especially with the arrival of next generation sequencing technologies, which have made whole genome resequencing and the 1000 Genomes Project feasible. [53][54][55] In recent years, many studies have been done to directly examine the associations of CNVs with complex diseases using SNP genotyping arrays.…”
Section: The Evolution Of Genetic Markers In Disease Gene Mappingmentioning
confidence: 99%
See 1 more Smart Citation